HUBUNGAN ANTARA JENIS KELAMIN DAN USIA TERHADAP KEJADIAN MYOPIA DI OPTIK ONE PALEMBANG TAHUN 2022 - Devi Susanti; Anisa (Jurnal Mata Optik, 2022)
Background: Myopia is a condition in which parallel rays that enter the eyeball are refracted by the refractive media in front of the retina. The inability of a person to see distant objects clearly or myopia can occur for several reasons. Objective: To know the relationship between gender and age simultaneously on the incidence of myopia at Optik One Palembang in 2021. Method: The type of research used in this study was a qualitative analysis with a Cross Sectional approach, in which the independent variable and the dependent variable were carried out at the same time. The sample of this study consisted of 124 respondents. Determination of the number of samples using the slovin formula and the sampling technique in this study was consecutive sampling. The refraction examination used a Snellen chart and trial lens and then followed by filling out the questionnaire. The hypothesis test used is chi square. Results: Gender, 87 respondents were female, there were 74 respondents (77.08) who were myopic and 13 respondents (46.42%) were not myopic, while from 37 male respondents there were 22 respondents (22.91%) who had myopia. and 15 respondents (53.57%) who were not myopic. Age was obtained from 89 respondents of risky age, there were 69 respondents (71.87%) who had myopia and 20 respondents (71.42%) who were not myopic. 27 respondents (28.12%) were myopic and 8 respondents (28.57%) were not myopic. The results of the Chi-square statistical test The relationship between gender and the incidence of myopia was found to be p value 0.000 and the relationship between age and the incidence of myopia was obtained p value 0.000.